An evaluation of alternative development strategies for Robusta coffee in Uganda - Liangzhi You; Simon Bolwig (Danish Institute for International Studies (DIIS), 2006)
Coffee is the most important export crop in Uganda and an important source of income for smallholder farmers in large parts of the country. The paper first investigates the challenges and opportunities faced by the Ugandan coffee industry, especially the decline in the world coffee market, changes in procurement strategies among coffee importers, the rapidly expanding market for high quality and specialty coffees, and the spread of the coffee wilt disease in Uganda. This leads us to examine possible development strategies for Ugandan coffee production within the general types 'production/productivity increase' or 'quality improvement'. Using IFPRI's Dynamic Research Evaluation for Management (DREAM) model, different scenarios for each type of strategy are evaluated to show their potential impacts on Ugandan export prices, export revenues, and producer gross benefits. We then discuss the constraints to and feasibility of development interventions that might achieve the simulated production and quality increases. Notwithstanding the oversupply of coffee in the world market, our analyses suggest that Uganda would benefit from moderately increasing Robusta coffee production as well as from enhancing bean quality and diversifying into sustainable coffees. High and reliable output must be accompanied with, and depend on, reductions in the unit cost of production in order to maintain or raise farm profitability and investment incentives given that prices are likely to remain low. An aggressive production growth strategy, on the other hand, would engage Uganda in a `race-to-the-bottom' competition with other producer countries if these adopt similar strategies. Quality interventions that focus on increasing bean size for mainstream coffee appear attractive due to the significant and direct effect of prices, the relatively low resource requirements of most technologies, and the added effects of larger beans on yields. Support to the production and marketing of differentiated coffees, particularly productions that combine organic and other sustainability certifications, also appear attractive. Such interventions should be carefully targeted, since relatively few farmers possess the necessary resources to produce for this market, and must be based on thorough market analysis given the high entry barriers to the specialty coffee market. The implementation of both productivity and quality enhancing strategies require a higher level of organization in the industry: horizontally among small farmers, and vertically among producers, traders, and roasters.
Keywords: 330; Kaffeeanbau; Uganda; Ökonometrisches Modell